Keefektifan Teknik Cognitive Restructuring untuk Meningkatkan Kejujuran Akademik Siswa Sekolah Menengah Atas - Rismawan, Kadek Sathya Gita; Gading, I Ketut; Asli, Luh (Buletin Konseling Inovatif, 2025)
A number of problems are seen as a result of poor academic honesty. This study aims to identify the efficiency of cognitive restructuring counseling in improving the academic honesty of senior high school students. By using A-B single subject reversal, the intervention was carried out by providing personal counseling using the cognitive restructuring technique. In collecting the data, we used Academic Honesty Psychological Scale, while the obtained data were analyzed using visual analysis. The findings indicate that individual counseling using cognitive restructuring is effective in enhancing students’ academic honesty. Also, positive self-perception and environment facilitate students to present high academic honesty and vice versa, as illustrated by the trend of higher academic honesty during the intervention phase.